Genetically encoded Ca2+ indicators in cardiac myocytes - Kästner, Lars; Scholz, Anke; Tian, Qinghai; Ruppenthal, Sandra; Tabellion, Wiebke; Wiesen, Kathrina; Katus, Hugo; Müller, Oliver J.; Kotlikoff, Michael I.; Lipp, Peter (Circulation research, 2014)
Genetically encoded Ca2+ indicators constitute a powerful set of tools to investigate functional aspects of Ca2+ signaling in isolated cardiomyocytes, cardiac tissue, and whole hearts. Here, we provide an overview of the concepts, experiences, state of the art, and ongoing developments in the use of genetically encoded Ca2+ indicators for cardiac cells and heart tissue. This review is supplemented with in vivo viral gene transfer experiments and comparisons of available genetically encoded Ca2+ indicators with each other and with the small molecule dye Fura-2. In the context of cardiac myocytes, we provide guidelines for selecting a genetically encoded Ca2+ indicator. For future developments, we discuss improvements of a broad range of properties, including photophysical properties such as spectral spread and biocompatibility, as well as cellular and in vivo applications.
Im Titel ist "2+" nach Ca hochgestellt
Gesehen am 24.09.2020